What is the quotient of (3x4 – 4x2 8x – 1) ÷ (x – 2)? 3x3 6x2 8x 24 – startfraction 47 over x minus 2 endfraction 3x3 6x2 8x 24 startfraction 47 over 3 x superscript 4 baseline minus 4 x squared 8 x minus 1 endfraction 3x3 6x2 8x 24 startfraction 47 over x minus 2 endfraction 3x3 6x2 8x 24 – startfraction 47 over 3 x superscript 4 baseline minus 4 x squared 8 x minus 1 endfraction

Respuesta :

The quotient of (3x⁴ - 4x² + 8x - 1) ÷ (x - 2) is 3x³ + 6x² + 8x + 24

It can be expressed as 3x³ + 6x² + 8x + 24  + 47 / x - 2

What are the Quotients?

Quotients is the number obtained by dividing one number by another.  

The given expression is;

(3x⁴ - 4x² + 8x - 1) ÷ (x - 2)

Using synthetic division:

(3x⁴ - 4x² + 8x - 1) / (x - 2)  = 3x³ + 6x² + 8x + 24 remainder 47

3x⁴ - 4x² + 8x - 1 → Dividend

x - 2 → Divisor

3x³ + 6x² + 8x + 24 → Quotient

47 → Remainder

The quotient is;

[tex]\rm =\dfrac{3x^4-4x^2+8x-1}{x-2}\\\\=\dfrac{(3x^3 + 6x^2 + 8x + 24)(x-2)}{x-2}\\\\=3x^3 + 6x^2 + 8x + 24[/tex]

Therefore, the quotient of (3x⁴ - 4x² + 8x - 1) ÷ (x - 2) is 3x³ + 6x² + 8x + 24

learn more on quotients:

brainly.com/question/13515262?

The quotient of (3x⁴ - 4x² + 8x - 1) ÷ (x - 2) would be 3x³ + 6x² + 8x + 24.

What are the Quotients?

Quotients are the number that is obtained by dividing one number by another number.

The given expression

(3x⁴ - 4x² + 8x - 1) ÷ (x - 2)

(3x⁴ - 4x² + 8x - 1) / (x - 2)  = 3x³ + 6x² + 8x + 24

remainder is 47

Here,

3x⁴ - 4x² + 8x - 1 = Dividend

x - 2 = Divisor

3x³ + 6x² + 8x + 24 = Quotient

47 = Remainder

The quotient is;

(3x⁴ - 4x² + 8x - 1) / (x - 2)

(3x⁴ - 4x² + 8x +24) (x - 2) / (x - 2)

3x³ + 6x² + 8x + 24

Therefore, the quotient of (3x⁴ - 4x² + 8x - 1) ÷ (x - 2) is 3x³ + 6x² + 8x + 24

learn more about quotients:

brainly.com/question/13515262?